1991
DOI: 10.1083/jcb.115.6.1737
|View full text |Cite
|
Sign up to set email alerts
|

Surface relocation of alpha 6 beta 4 integrins and assembly of hemidesmosomes in an in vitro model of wound healing.

Abstract: Abstract. A transmembrane extracellular matrix receptor of the integrin family, a684, is a component of the hemidesmosome, an adhesion complex of importance in epithelial cell-connective tissue attachment

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
69
0

Year Published

1993
1993
2003
2003

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(73 citation statements)
references
References 33 publications
4
69
0
Order By: Relevance
“…receptor for laminin (35,54,55 We have extended previous studies (19)(20)(21)(22) by demonstrating that HER-2/neu and HER-3 are both expressed in skin and dermal adnexa. We have also shown that HER-2/neu expression is markedly decreased in the migrating new epidermis, while neoepidermal HER-3 expression is markedly increased.…”
Section: Discussionmentioning
confidence: 51%
“…receptor for laminin (35,54,55 We have extended previous studies (19)(20)(21)(22) by demonstrating that HER-2/neu and HER-3 are both expressed in skin and dermal adnexa. We have also shown that HER-2/neu expression is markedly decreased in the migrating new epidermis, while neoepidermal HER-3 expression is markedly increased.…”
Section: Discussionmentioning
confidence: 51%
“…The a6134-integrin localizes in hemidesmosomes (20-23) but it is not restricted to that location. It was recently shown that in an in vitro model ofwound healing, a614 appears along the entire cell surface of migrating keratinocytes in which the hemidesmosomes are absent (21 ). Epiligrin serves as a good candidate for a ligand for a614 in migrating keratinocytes.…”
Section: Discussionmentioning
confidence: 99%
“…The a331-integrin has been reported to bind several ligands, namely fibronectin, collagen, laminin, and epiligrin (5,14,15,19). The a6134-integrin localizes in hemidesmosome structures (20)(21)(22)(23), probably binding to epiligrin (24) or kalinin (25) present in the anchoring filaments. Finally, the acv#5-integrin mediates keratinocyte adhesion on vitronectin ( 14).…”
Section: Introductionmentioning
confidence: 99%
“…α6β4 integrin has generally been viewed as a mediator of attachment and HD formation at sites more distal from the wound edge (Kurpakus et al, 1991;Nguyen et al, 2000a) or even as an inhibitor of keratinocyte motility (Hintermann et al, 2001). However, several lines of evidence suggest α6β4 integrin may play a more direct and active role in keratinocyte migration.…”
Section: Introductionmentioning
confidence: 99%
“…We believe that it is unlikely that keratinocytes make isolated contact between collagen I and α2β1 integrin at the front edge of a wound. Indeed, leading cells highly express unprocessed laminin-5, and upregulate expression of many integrins including α2β1, α3β1 and α6β4 (Kainulainen et al, 1998;Kurpakus et al, 1991;Larjava et al, 1993). Therefore, growth factor-induced chemotactic signals must be translated from several of these inputs into a functionally coordinated response.…”
Section: Direct Activation Of α3β1 Integrin Though β4(ad)mentioning
confidence: 99%